Poxvirus multiprotein entry–fusion complex - Senkevich, Tatiana G. (National Academy of Sciences, 2005)
Poxviruses have evolved elaborate mechanisms for cell entry, assembly, and exocytosis. Recently, four vaccinia virus membrane proteins, namely A21, A28, H2 and L5, were reported to be necessary for cell entry and virus-induced cell–cell fusion but not for virion morphogenesis or attachment of virus particles to cells. Using immunoaffinity purification followed by mass spectrometry, we now show that these four proteins as well as four additional previously uncharacterized putative membrane proteins (A16, G3, G9, and J5) form a stable complex. These proteins fall into two groups: A21, A28, G3, H2, and L5 have an N-terminal transmembrane domain, 0–2 intramolecular disulfide bonds, and no sequence similarity, whereas A16, G9, and J5 have a C-terminal transmembrane domain and 4–10 predicted disulfide bonds and are homologous. Studies with conditional-lethal null mutants indicated that the viral membrane was crucial for assembly of the complex and that the absence of individual polypeptide components profoundly decreased complex formation or stability, suggesting a complicated interaction network. Analysis of purified virions, however, demonstrated that the polypeptides of the complex trafficked independently to the viral membrane even under conditions in which the complex itself could not be isolated. All eight proteins comprising the entry–fusion complex are conserved in all poxviruses, suggesting that they have nonredundant functions and that the basic entry mechanism evolved before the division between vertebrate and invertebrate poxvirus species.